Pendidikan Karakter Berbasis Al-Qur’an; Upaya Menciptakan Bangsa yang Berkarakter - Amri Rahman; Dulsukmi Kasim (Al-Ulum, 2014)
This paper discusses about the issue of educational character. This issue is sounding in educational sector as a response to any forms of moral decrease of Indonesia as a nation. Al-Qur’an contains teachings to educate human in order to be a good nation. Its main example is the Prophet Muhammad Saw and his exemplary followers. The educational character which is based on the Quran basically is built through three dimensions: attitude to the Supreme Creator (Allah SWT), attitude to ourselves, and attitude to the others and our environment. Indonesians national identity which has been good character is indicated in the Qur’an with some criteria, namely: unity; that is, to have agreed noble values; work hard, means discipline and good time management, caring; moderate and open minded; ready for struggle and be brave and patient in facing some challenges. Therefore, to define address the educational character based on the Qur’an in the establishing nationhood mostly depends on the roles of: 1) society through strong faith and examples from the Prophet Muhammad Saw; 2) Educational sector through schools and mosques; and 3) the government.